Drosophila Activin-beta and the Activin-like product Dawdle function redundantly to regulate proliferation in the larval brain. - Zhu, C.C.; Boone, J.Q.; Jensen, P.A.; Hanna, S.; Podemski, L.; Locke, J.; Doe, C.Q.; O'Connor, M.B. (Development, 2008)
The Drosophila Activin-like ligands Activin-beta and Dawdle control several aspects of neuronal morphogenesis, including mushroom body remodeling, dorsal neuron morphogenesis and motoneuron axon guidance. Here we show that the same two ligands act redundantly through the Activin receptor Babo and its transcriptional mediator Smad2 (Smox), to regulate neuroblast numbers and proliferation rates in the developing larval brain. Blocking this pathway results in the development of larvae with small brains and aberrant photoreceptor axon targeting, and restoring babo function in neuroblasts rescued these mutant phenotypes. These results suggest that the Activin signaling pathway is required for producing the proper number of neurons to enable normal connection of incoming photoreceptor axons to their targets. Furthermore, as the Activin pathway plays a key role in regulating propagation of mouse and human embryonic stem cells, our observation that it also regulates neuroblast numbers and proliferation in Drosophila suggests that involvement of Activins in controlling stem cell propagation may be a common regulatory feature of this family of TGF-beta-type ligands.